Composition determination for electron beam irradiation and ionic liquid pretreatment of Oil Palm Frond (OPF): article - Mohd Zamri, Siti Aisyah; Azizan, Amizon; Jusri, Nur Amira Aida (2018)
The determination of the composition of lignocellulosic biomass is a critical means in determining the efficiency of a pretreatment prior to conversion of bioethanol. In this literature, the effect of electron beam irradiation and ionic liquid as pretreatment of a lignocellulosic biomass is investigated. The lignocellulosic biomass used in this literature is Oil Palm Frond (OPF) and pure cellulose as control.